1985
DOI: 10.1002/jor.1100030114
|View full text |Cite
|
Sign up to set email alerts
|

Binding sites in fetal and growth plate cartilage

Abstract: In addition to genetic and nutritional factors, linear growth during the prenatal and postnatal periods is controlled by peptide, steroid, and thyroid hormones interacting with the receptors present on the membrane or in the cytosol and nuclei of growth plate cartilage. Using standard procedures, insulin and "nonsuppressible insulin-like activity" (a somatomedin) showed significant binding in 600, 15,000, and 105,000 g membrane fractions of epiphyseal cartilage of immature animals. The binding of growth hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We have found parallel evidence, in both the Pond-Nuki dog model of OA (15) and in rheumatoid arthritis in humans (14), that low-dose, oral steroids block a rise in cartilage neutral metalloprotease activity. It may be that steroids coordinate the regulation of all metalloproteases in cartilage, regardless of whether this regulation is mediated by the suppression of synovial factors (15) or by direct action o n the chondrocytes (21). This question awaits further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…We have found parallel evidence, in both the Pond-Nuki dog model of OA (15) and in rheumatoid arthritis in humans (14), that low-dose, oral steroids block a rise in cartilage neutral metalloprotease activity. It may be that steroids coordinate the regulation of all metalloproteases in cartilage, regardless of whether this regulation is mediated by the suppression of synovial factors (15) or by direct action o n the chondrocytes (21). This question awaits further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…It is conceivable that energy dissipated during the loading history could alter the catabolism or anabolism of hormone receptors in the tissues. Cruess (9) showed that the concentration of hormone receptors is variable in different regions of the chondroepiphysis and speculated that these variations could be related to skeletal morphogenesis.…”
Section: Mechanical-chemical Interactionsmentioning
confidence: 99%